THE SPIRITUALITY OF NGARUPUK TRADITION IN JAVANESE AND BALINESE HINDU CULTURE IN WAY PANJI DISTRICT, SOUTH LAMPUNG - Faiz Susena Faiz; Muslimin Muslimin; Nofrizal Nofrizal (Religi: Jurnal Studi Agama-agama, 2026)
The Ngarupuk tradition is an important Hindu ritual performed before Nyepi Day as a means of purifying oneself and the environment from negative influences. The differences in the implementation of Ngarupuk in the Javanese and Balinese Hindu communities in Way Panji District, South Lampung, indicate variations in symbolism and spiritual meaning that are interesting to study. This study aims to analyze the spiritual meaning and symbolism of the Ngarupuk tradition in both communities. The study used a qualitative approach with data collection techniques such as observation, in-depth interviews, and documentation. The analysis is based on the theory of religious symbolism, which views rituals as a medium for conveying spiritual meaning through cultural and religious symbols. The results show that the Javanese Hindu community performs Ngarupuk simply by emphasizing a contemplative atmosphere, the use of torches, kentongan (a wooden drum), and minimalist symbols that represent the release of negative traits in humans. Meanwhile, the Balinese Hindu community performs Ngarupuk with a more complex procession through an ogoh-ogoh parade, offering rituals, and various traditional symbols that reflect the human struggle against negative forces. Despite differences in implementation, both communities share the same spiritual goals: self-purification, self-control, and strengthening one's relationship with God. The Ngarupuk tradition also plays a role in maintaining religious identity, strengthening social solidarity, and supporting harmonious multicultural life in Way Panji District. Keywords:Ngarupuk, cultural dynamics, religious rituals   Tradisi Ngarupuk merupakan salah satu ritual penting dalam agama Hindu yang dilaksanakan menjelang Hari Raya Nyepi sebagai sarana penyucian diri dan lingkungan dari pengaruh negatif. Perbedaan bentuk pelaksanaan Ngarupuk pada komunitas Hindu Jawa dan Hindu Bali di Kecamatan Way Panji, Lampung Selatan, menunjukkan adanya variasi simbolisme dan pemaknaan spiritual yang menarik untuk dikaji. Penelitian ini bertujuan untuk menganalisis makna spiritual dan simbolisme tradisi Ngarupuk pada kedua komunitas tersebut. Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dan dokumentasi. Analisis penelitian didasarkan pada teori simbolisme religius yang memandang ritual sebagai media penyampaian makna spiritual melalui simbol-simbol budaya dan keagamaan. Hasil penelitian menunjukkan bahwa masyarakat Hindu Jawa melaksanakan Ngarupuk secara sederhana dengan menekankan suasana kontemplatif, penggunaan obor, kentongan, dan simbol-simbol minimalis yang merepresentasikan pelepasan sifat-sifat negatif dalam diri manusia. Sementara itu, masyarakat Hindu Bali melaksanakan Ngarupuk dengan prosesi yang lebih kompleks melalui pawai ogoh-ogoh, ritual persembahan, dan berbagai simbol adat yang mencerminkan perjuangan manusia melawan kekuatan negatif. Meskipun terdapat perbedaan dalam bentuk pelaksanaan, kedua komunitas memiliki tujuan spiritual yang sama, yaitu penyucian diri, pengendalian diri, serta penguatan hubungan manusia dengan Tuhan. Tradisi Ngarupuk juga berperan dalam menjaga identitas religius, mempererat solidaritas sosial, dan mendukung terciptanya keharmonisan kehidupan multikultural di Kecamatan Way Panji. Kata kunci: Ngarupuk, dinamika budaya, ritual keagamaan